Efforts to develop aspects of cognitive ability for early childhood based on Western and Eastern concepts - Meriyati, Meriyati; Wulandari, Heny; Aisya, Nadiya (Universitas Islam Negeri Raden Intan Lampung, 2022)
Cognitive development is one of the important elements for child development. this is where the reasoning lies that the child will go through during his lifetime. This study aimed to discover the efforts in developing aspects of children's cognitive abilities based on western and eastern concepts. The method used is classroom action research using two cycles. Playing activities are carried out to empower all the potential they have so that it is hoped that, in the future, they will be able to actualize themselves in society. Teachers made various efforts to develop aspects of cognitive abilities in early childhood by referring to theories put forward by experts from both western and eastern theories. From the research findings obtained by researchers, namely children accustomed to home visit activities, children's cognitive abilities have reached 75%. Based on the study's results, it was found that in cycle one, the children began to develop and was not yet developing. Then, it was continued with the 2nd cycle to meet the targets set by the researchers, which resulted in the child's cognitive development developing well.